Meningkatkan Kemampuan Membaca Permulaan Anak Usia Dini dengan Media Kartu Huruf Kelompok B TK Negeri Pembina Mataram - Syamsiah, Syamsiah (ANWARUL, 2022)
This classroom action research aims to determine the improvement of Early Childhood Reading Skills with Media Cards for Group B Kindergarten Negeri Mataram Pembina Odd Semester for the 2021/2022 Academic Year. The subjects of this study were 15 students of group B of the State Pembina Mataram Kindergarten, consisting of 8 female students and 7 male students. This research uses action research in two cycles consisting of four stages, namely: design, activity and observation, reflection. The results based on research and discussion can be opened that the initial reading ability in children aged 5-6 years TK Negeri Pembina Mataram can be improved using picture word cards media. This can be proven from the results of increasing the original reading ability. In the initial conditions the average achievement was 70.56% and an increase of 13.34% so that in Cycle I it reached 71.11% and in Cycle I to Cycle II it increased by 33.33% so that in Cycle II it reached a score of 100 %.